Effects of high intensity aerobic training on symptomatology of primary dysmenorrhoea - Imtiaz, Iqra; Riaz, Huma (Journal of the Pakistan Medical Association, 2022)
This study was conducted to determine the effects of high-intensity aerobic training on the symptomatology of primary dysmenorrhoea. The study was conducted at Shifa Tameer-e-Millat University, Islamabad, Pakistan, from February 2021 to July 2021. The participants were randomly allocated to two groups—experimental and control—with 21 participants in each group, using the sealed envelope method. Experimental group underwent a structured eight-week high-intensity aerobic training regimen on a treadmill (Intensity 80-90% of target heart rate). The participants in the control group were given low-intensity aerobic training (Intensity 40-60% of target heart rate). The severity of dysmenorrhoea symptoms was assessed using Menstrual Symptom Questionnaire. The study concluded that high-intensity aerobic training is effective in reducing the symptoms of primary dysmenorrhoea. Keywords: Dysmenorrhoea, Heart rate, Pakistan, Primary, Participant, University.